Shallow-water Campanulariidae (Hydrozoa, Leptothecatae) from Northern Bahía, Brazil - Kelmo, Francisco (2003)
This study provides the first semi-quantititative account of the benthic campanulariid hydroids from Northern Bahia (Brazil), down to a depth of 60 m, based largely on collections obtained since 1992. Colonies were collected from six habitats along the coast of Salvador City, Todos os Santos Bay, Itaparica Island and at the northernmost part of the coast of the State of Bahia. From the 982 colonies examined, nine species were recorded: Campanularia hincksii, Clytia gracilis, C. hemisphaerica, C. hummelincki, C. linearis, C. macrotheca, C. noliformis, Obelia bidentata and O. dichotoma. Following a defined abundance scale, Clytia gracilis and C. noliformis were the most abundant species, whereas Campanularia hincksii and Clytia hummelincki were rare. Cluster analysis of relative abundance data revealed sandy shores had a markedly different hydroid community from other habitats. A simplified identification key, redescriptions, illustrations and data on nematocyst compliment are provided for each species. Campanularia hincksii, Clytia macrotheca and C. noliformis are reported from Brazil for the first time.